Constraints and Techniques for Improving Pulses Production in Tamil Nadu, India - Amutha, D. (International Journal of Bio-resource and Stress Management, 2023)
Production of pulses and its consumption are important in maintaining food and nutritional security. Pulses contain higher protein compared to any other grains and vegetables. This paper analyses the status and constraints of pulses production and the techniques including role of extension services for improving production in the areas under study in Tuticorin, Tirunelveli and Madurai district of Tamil Nadu. In 2010, a total of 648 respondents were selected using stratified random sampling from different categories of farming community. Statistical analytical tools like standard error, standard deviation, trend analysis, variance, chi-square tests, t-tests, Cramer’s V test, etc. were used for interpretation of data. The reasons of low production and productivity, according to farmers’ perceptions, were due to use of poor quality seed, low area coverage, poor management, inadequate irrigation facilities, low investment, etc. Use of improved seed, adoption of optimum cropping pattern, maintenance of quality germ plasm, application of nutrients in the soil through micro-nutrient, bio-fertilizer, organic manures, adoption of crop protection measures, etc. are some of the important points which need immediate attention. Provision of appropriate marketing infrastructures and facilities is another important area for increasing production.